Yield component Responses to different Planting methods in Fonio under rain fed conditions - Isong, A.; Umar, F. A.; Mohammed, I. G.; Bashir, M. N.; Dachi, S. N.; Mamza, W. S.; Isong, C.; Jimoh, R.; Bake, J.; Onotugoma, E.; Aremu, P. A. (BADEGGI JOURNAL OF AGRICULTURAL RESEARCH AND ENVIRONMENT, 2023)
Abstract Fonio respond differently at different sowing conditions. Field experiment was conducted to assess the respond of fonio grain yield and its components when subjected to different seeding methods under rainfed condition during the growing season of 2021 and 2022. The Randomized complete block design with three replications was adopted for the experiment. The result revealed that planting methods (dibbling, drilling broadcasting and transplanting) used had significant effect on all the yield components and grain yield. Transplanting was on a clear lead with an average number of tillers per plant of 13.8 surpassing dibbling and drilling whose average had no significant difference at 5% probability level. In days to maturity, transplanted crops takes longer (115.1) days for fonio to reach 50% flowering. However, fonio appears to mature earlier when drilling and transplanting methods are adopted. Taller plants, longer spikes, longer panicles, higher number of tillers and higher grain yield were observed when transplanting method was applied in fonio field cultivation. Therefore, transplanting method could be recommended for increased tillers, longer spikes and higher grain yield of fonio under rainfed condition.